(untitled) (The Nepali Mathematical Sciences Report, 2024)
This work aims to introduce and study new classes of generalized Cesàro summable vector-valued sequence spaces of bounded type. Besides exploring the completeness of the classes Ces(X, p) and Ces(X, p) ∞ when topologized with suitable natural p-normed, our primary interest is to study the β-dual of Ces(X, p).